2021
DOI: 10.1155/2021/6631981
|View full text |Cite
|
Sign up to set email alerts
|

Numerical Simulation of Fine Particle Solid‐Liquid Two‐Phase Flow in a Centrifugal Pump

Abstract: To study the effect of fine particle size and volume concentration on the performance of solid-liquid two-phase centrifugal pump, the mixture multiphase flow model, RNG k-ε turbulence model, and SIMPLEC algorithm were used to simulate the two-phase flow of the centrifugal pump. The effects of particle size and volume concentration on internal pressure distribution, solid volume distribution, and external characteristics were analyzed. The results show that under the design discharge conditions, with the increa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(8 citation statements)
references
References 38 publications
0
6
0
Order By: Relevance
“…In consideration of the influence of the interphase drag force and slip velocity, the heterogeneous flow model was adopted, while for the interphase drag force, we adopted the Schiller-Naumann model. 19 The Eulerian-Lagrange model was used to calculate the internal flow of a solid-liquid two-phase centrifugal pump. The governing equations were continuity equation and Reynolds time mean RANS momentum conservation equation.…”
Section: Numerical Calculation Methods and Boundary Conditionsmentioning
confidence: 99%
“…In consideration of the influence of the interphase drag force and slip velocity, the heterogeneous flow model was adopted, while for the interphase drag force, we adopted the Schiller-Naumann model. 19 The Eulerian-Lagrange model was used to calculate the internal flow of a solid-liquid two-phase centrifugal pump. The governing equations were continuity equation and Reynolds time mean RANS momentum conservation equation.…”
Section: Numerical Calculation Methods and Boundary Conditionsmentioning
confidence: 99%
“…Some studies have simulated the solid-liquid two-phase flow to predict the trajectory of particles in a pump [7,8]. Wang et al used the particle model to analyze the internal flow field characteristics of a centrifugal pump transporting solid-liquid twophase flow [9]. Gandhi et al proposed a new method to analyze the flow characteristics of flow passage components based on the characteristics of the slurry pump [10].…”
Section: Introductionmentioning
confidence: 99%
“…Chen et al (1999) found that the jet wake structure near the impeller outlet is an important cause of local erosion through the experiment of solid-liquid two-phase flow of centrifugal pump. Wang et al (2013) used a particle model to simulate the solid-liquid twophase flow in centrifugal pump, focusing on the analysis of the relationship between slip velocity, volume fraction distribution and erosion of flow-through parts. Wen et al (2019) used the Euler-Lagrange model and Finnie erosion model to simulate the solid-liquid twophase flow in the pump.…”
Section: Introductionmentioning
confidence: 99%